The effect of damage on the energy absorption potential of composite structures - Bailey, D.A. (2005)
This thesis describes work undertaken to investigate the effects of damage on the energy absorption potential of composite tubes. Tubes of various geometries and manufactured from either continuous filament random mat (CoFRM) or glass braid and polyester resin were subjected to various types of damage before testing. Damage types consisted of drilled holes, to simulate the use of drilling components for the need of assembly, impacts, to simulate damage that may occur through tool drops or items being kicked up during use and PET inserts to simulate delamination.